The Changing Landscape of Urologic Practice, An Issue of Urologic IR: 2022 (Bangladesh Journal of Urology, 2023)
Interventional Uroradiology or Urological IR covers various minimally invasive procedures to treat problems that affect the kidney, bladder and ureter (the tube connecting the kidney to the bladder), and testes.Almost all patients in the UK with obstructed and/or infected kidneys are referred to interventional radiology for percutaneous nephrostomy and/or placement of an anterograde JJ stent. Although this ‘tradition’ is going strong in the UK, urologists worldwide have evolved their practice to encompass such interventional procedures in their remit.1Advances in imaging technology, especially in the last two decades, have led to a paradigm shift in the field of image-guided interventions in urology. While the traditional biopsy and drainage techniques are firmly established, image-based stone management and endovascular management of hematuria have evolved further. Ablative techniques for renal and prostate cancer and prostate artery embolization for benign prostatic hypertrophy have evolved into viable alternative treatments. Many urologic diseases that were earlier treated surgically are now effectively managed using minimally invasive image-guided techniques, often on a daycare basis using only local anaesthesia or conscious sedation. This article presents an overview of the technique and status of various image-guided urological procedures, including recent emerging techniques.Bangladesh J. Urol. 2022; 25(2): 106-121